Sustainability Analysis of Seaweed Cultivation as Regional Economic Resource in Raijua District - Ludji, Frengky Saputra; Nalle, Agus Arnold; Ballo, Fransina W. (Jurnal Ekonomi Balance, 2025)
This study investigates the sustainability of seaweed cultivation as a strategic economic resource and its implications for community welfare in Raijua District, Sabu Raijua Regency, Indonesia. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation involving key stakeholders, including seaweed farmers, local authorities, and marine experts. The research aims to explore the socio-economic, environmental, and institutional factors influencing the sustainability of seaweed farming, and to assess its potential in supporting regional economic development. Findings reveal that the sustainability of seaweed cultivation is shaped by multiple interrelated factors such as environmental conditions, site selection, cultivation technology, farmer management skills, market access, infrastructure, government policy, education, and institutional collaboration. These factors directly affect productivity, resilience, and the long-term viability of seaweed farming. The study also highlights the positive impacts of seaweed cultivation on community welfare through income generation, reduced urban migration, empowerment of marginalized groups, economic diversification, and the growth of micro and small enterprises. Furthermore, environmentally friendly cultivation practices contribute to marine ecosystem conservation, carbon sequestration, and sustainable resource management. The study concludes that seaweed cultivation, when supported by integrated policy frameworks and stakeholder cooperation, can serve as a sustainable livelihood strategy and an engine for regional economic growth. These insights are valuable for policymakers, development practitioners, and researchers focusing on sustainable aquaculture and coastal economic resilience in developing regions.